IMPLEMENTASI PEMBELAJARAN SIKLUS AKUNTANSI PERUSAHAAN JASA UNTUK MENINGKATKAN PEMAHAMAN SISWA SMA NEGERI 2 JAKARTA - Ruby Ng; Chelsya (Jurnal Serina Abdimas, 2026)
Teaching Assistance in Educational Institutions is one of the programs under Merdeka Belajar Kampus Merdeka (MBKM), in which university students have the opportunity to share their knowledge within educational institutions. The teaching activity carried out in this program focuses on training in the accounting cycle of service companies. This activity is expected to be beneficial and broaden the students’ knowledge.The teaching of accounting is considered essential since accounting is fundamentally one of the economic sciences that is practiced by individuals in their daily lives. The training provided on the accounting cycle of service companies aims to equip students with a basic understanding of how to manage and account for finances properly, whether for personal use, small businesses, or larger corporations. The accounting cycle provides both conceptual and practical understanding of how financial transactions are managed in a systematic and structured manner. Through this process, students are able to understand the flow of financial information starting from recording, posting, and preparing trial balances, up to the preparation of financial statements.This program was conducted over a period of four months, from August to November, at SMA Negeri 2 Jakarta Barat. Considering the limited time and school curriculum, where accounting is only introduced at the twelfth-grade level, it is crucial to implement an innovative, interactive, and practical approach to teaching.The program also provides various benefits, such as offering new experiences and developing critical thinking skills when responding to students’ questions. Moreover, this activity serves as an opportunity to introduce and provide students with basic knowledge of accounting, which is expected to be useful in shaping and determining their future goals. Asistensi mengajar di satuan pendidikan adalah salah satu program Merdeka Belajar Kampus Merdeka (MBKM) dimana mahasiswa dapat berbagi pengetahuan yang mereka miliki di satuan pendidikan. Pengajaran yang dilakukan berupa pelatihan siklus akuntansi perusahaan jasa. Pengajaran ini diharapkan bermanfaat dan menambah wawasan siswa-siswa tersebut. Pengajaran ini dianggap penting mengingat pada dasarnya akuntansi merupakan salah satu ilmu ekonomi yang dilakukan oleh setiap manusia di kesehariannya. Pengajaran yang dilakukan adalah pelatihan siklus akuntansi perusahaan jasa yang bertujuan untuk memahami dasar mengelola dan mempertanggungjawabkan keuangan secara benar baik untuk diri sendiri, usaha kecil, maupun perusahaan besar. Siklus akuntansi ini memberikan pemahaman konseptual dan praktis mengenai transaksi keuangan yang dikelola secara runtut dan sistematis. Melalui proses tersebut, siswa dapat memahami alur keuangan mulai dari pencatatan, penggolongan, dan penyusunan neraca saldo, hingga pembuatan laporan keuangan. Kegiatan ini dilakukan selama empat bulan dimulai dari bulan agustus sampai November di SMA Negeri 2 Jakarta Barat. Melihat adanya keterbatasan waktu dan kurikulum yang menyebabkan penyampaian materi akuntansi di sekolah baru diperkenalkan di kelas XII, pembelajaran yang inovatif, interaktif, dan praktis menjadi hal yg penting untuk diterapkan. Dengan adanya program ini memberikan sejumlah manfaat berupa pengalaman baru dan kemampuan berpikir kritis dalam menghadapi pertanyaan-pertanyaan yang diberikan oleh siswa-siswa. Selain itu, kegiatan ini juga bermanfaat untuk membekali dan memperkenalkan ilmu akuntansi kepada siswa-siswa yang diharapkan dapat bermanfaat untuk menentukan tujuan masa depan mereka.